Integrating humanization in health professional training through clinical simulation: A review of the literature - Infante-Peñafiel, Alicia Cecilia (2025)
The increasing automation and standardization of healthcare have raised concerns about the risk of dehumanization, affecting both patient trust and professional well-being. Humanization, understood as the integration of technical proficiency with the recognition of patient dignity, has become a key priority in health professions education. Within this context, clinical simulation has emerged as an effective pedagogical tool for fostering empathy, communication, and other humanistic competencies among students in the health sciences. This review analyzes the literature on the use of simulation as a tool to teach humanization in healthcare, identifying key strategies and evaluating their impact. Findings highlight that the use of standardized patients, realistic scenarios, and reflective debriefing enhances students' ability to provide person-centered care. Although simulation has proven effective in teaching empathy and communication, significant gaps remain regarding its long-term impact and its implementation across various health disciplines. It is recommended to integrate humanization into simulation-based curricula and to develop standardized methods of assessment. Promoting an educational culture grounded in humanistic values is essential for improving the quality of care and the satisfaction of both patients and healthcare professionals.